THE EFFECT OF SERVICE QUALITY ON USER SATISFACTION OF ROLL ON ROLL OFF (RO-RO) SHIPS - Nadia Angraini (Jurnal Ekonomi, 2022)
The purpose of this study was to determine the effect of service quality on the satisfaction of service users. Tangibles, Responsiveness, Reliability, Assurance, and Empathy were some of the assessment indicators utilized. This study was conducted at PT. Jembatan Nusantara, which is located at the crossing port of the Air Putih-Selari River in the Bengkalis Regency. The quantitative data from this study was collected from a primary data source, or data that was gathered directly from the subject of the study. Users of the Air Putih-Selari River (RO-RO) ships service made up the entire study population. The questionnaire utilized for data collection in this study was given to the users of two PT. Jembatan Nusantara-owned operating ships, and samples were taken using the incidental sampling technique, which relies on chance encounters between potential respondents and the researcher. There is total of 200 respondents made up this study's sample. The researcher utilized SPSS V.22.00 as a statistical tool. The analytical methods utilized were the t test, correlation coefficient, determination coefficient, simple linear regression test, validity test, reliability test, and simple test. According to the study's findings, there was a relationship between service quality (X) and service user satisfaction (Y), with a correlation coefficient of 89.9%, a coefficient of determination of 79.4%, and a significance level of 0.05 for the t test results.